The Impact of Recent Advances in Endoscopic Ultrasound-Guided Tissue Acquisition on the Management of Pancreatic Cancer - Marques,Susana (2021)
Abstract: Over the last few decades, endoscopic ultrasound (EUS)-guided tissue acquisition has become the method of choice for the pathological diagnosis of solid pancreatic lesions. Due to its high diagnostic yield and low complication rate, EUS-guided tissue acquisition has surpassed percutaneous sampling techniques. For many years, EUS-guided fine-needle aspiration (EUS-FNA) was traditionally used to obtain cytological aspirates of solid pancreatic lesions, with sensitivity values ranging from 80 to 90% for the diagnosis of malignancy. Nevertheless, despite numerous technical advances, EUS-FNA still presents some limitations. Therefore, EUS-guided fine-needle biopsy (EUS-FNB) has been introduced to provide tissue core biopsies, allowing histological assessment. A newly developed generation of FNB needles has demonstrated an outstanding diagnostic accuracy of over 95% for solid pancreatic lesions and provides samples appropriate for ancillary testing, such as immunohistochemistry and tumour molecular profiling. As a result, EUS-FNB is rapidly replacing EUS-FNA and is now the recommended technique for EUS-guided tissue acquisition in pancreatic cancer. Furthermore, with the recent expansion of neoadjuvant treatment criteria and with the advent of novel and personalised anti-cancer therapies, EUS-FNB is gaining a pivotal role in pancreatic cancer management and might soon be generalised to all patients, independent of disease stage. In this article, the authors present an updated review of the role of EUS-guided tissue acquisition in pancreatic cancer. Current indications, several technical aspects and new applications of EUS-FNA and EUS-FNB are discussed.